Catchment hydrology, resources, economics and management (ChREAM): Integrated modelling of rural land use & farm income impacts of the WFD and its potential non-market benefits - Ian J. Bateman; Roy Brouwer; Helen Davies; Day. Brett H.; Amelie Deflandre; Salvatore Di Falco; Stavros Georgiou; David Hadley; Michael Hutchins; Andrew P. Jones; David Kay; Graham Leeks; et al. (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2006)
The paper outlines a programme of research funded under the Rural Economy and Land Use (RELU) programme. The proposed research will examine the likely effects of the Water Framework Directive (WFD) in terms of both its impacts upon the farming sector and the non-market benefits it may generate. From an agricultural perspective the WFD will impose a substantial extension of controls upon diffuse pollution from farms. A major objective of the research will be to assess the likely response and consequent economic costs to an already fragile farming sector. This objective will be addressed via a highly interdisciplinary methodology combining hydrological and other physical sciences with quantitative and qualitative socio-economic analyses to generate an integrated hydrological-economic model of farm activities and incomes. This will dynamically link farm local and regional activities to water standards, allowing feedback loops to indicate the impacts of altering farm activity and changing water quality targets. Model parameters and response scenarios will initially be established via quantitative estimation and then refined through a series of farm attitude and behaviour surveys. This cost-effectiveness analysis will be complemented by an assessment of the benefits arising from the WFD and an aggregation and equity analysis of the distribution of both costs and benefits. Planned deliverables include assessments of the impact of alternative WFD implementation strategies allowing policy makers to inspect effects upon farmer and the wider community at a variety of spatial scales.
Keywords: 330